PEMBENTUKAN POLA PENGAMBILAN MATA KULIAH MENGGUNAKAN ALGORITMA FREQUENT PATTERN TREE - Ester Ester (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The application aims to make the data stored courses by the university student becomes more compact due to the pattern of courses so that the data in the database can be stored and processed in less time. The application uses Frequent Pattern Tree (FP-tree) algorithm which is used to create a tree that shows frequent items list (list of data subjects). The experiment results showed that the total records of new application is more compact than old application, the average time to save data into the database requires less time by using new application and the average time of university students attendance list report data processing requires less time by using new application. However the average time of Kartu Studi Mahasiswa (KSM) report data processing takes a little longer than old application, this’s because the root (subject parent) inspection process to every subject pattern which is formed in polamatakuliah table. Key wordsFP-Growth, Frequent Itemset, Frequent Pattern Tree, PHP, Pola Mata Kuliah